2021
DOI: 10.3390/f12060743
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Fungi and Yeasts Associated with Mites Phoretic on Ips typographus in Eastern Finland

Abstract: The European spruce bark beetle (Ips typographus) has become a major forest pest in Finland in recent years. The beetle is a well-known vector of mainly ophiostomatoid fungi causing blue-stain of timber and pathogens that have the ability to amplify the insect damage. It also vectors other associated organisms, such as phoretic mites. The ecology of these mites remains poorly understood, including their associations with fungi. In this study, we considered filamentous fungi and yeasts associated with mites pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Meyerozyma guilliermondii was captured by us only from cultivation and it was also recorded in the microbiome of ambrosia beetle Platypus koryoensis (Yun et al 2015), where also its enzymatic capability of plant tissue degradation was detected.Wickerhamomyces bisporus was previously found in association withI. typographus (Giordano et al 2012) and is also the dominant yeast species found on phoretic mites of the same beetle species (Linnakoski et al, 2021). Species of Wickerhamomyces have been also reported from galleries and guts of wood-boring insects (Hui et al 2013;Ninomiya et al 2013), indicating their common association with beetles.…”
Section: Discussionmentioning
confidence: 84%
“…Meyerozyma guilliermondii was captured by us only from cultivation and it was also recorded in the microbiome of ambrosia beetle Platypus koryoensis (Yun et al 2015), where also its enzymatic capability of plant tissue degradation was detected.Wickerhamomyces bisporus was previously found in association withI. typographus (Giordano et al 2012) and is also the dominant yeast species found on phoretic mites of the same beetle species (Linnakoski et al, 2021). Species of Wickerhamomyces have been also reported from galleries and guts of wood-boring insects (Hui et al 2013;Ninomiya et al 2013), indicating their common association with beetles.…”
Section: Discussionmentioning
confidence: 84%
“…Several species of yeasts (e.g., Kuraishia molischiana (0.42%), Wickerhamomyces bisporus (0.22%)) were also detected, which were previously shown to be associated with different bark beetles such as Ips typographus or Dendroctonus sp. [53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the limitations of testing pure single-species cultures under field conditions. In the breeding galleries constructed by the beetles, several closely related species of ophiostomatoid fungi and yeasts co-inhabit the phloem of the bark ( Giordano et al, 2013 ; Linnakoski et al, 2021 ). Therefore, one approach would be to analyze mixed microbial cultures in their natural growth substrates together with pheromones in field traps.…”
Section: Discussionmentioning
confidence: 99%